Oligomer-Assisted Photoactive Layers Enable >18 % Efficiency of Organic Solar Cells - Cheng, Yujun; Huang, Bin; Huang, Xuexiang; Zhang, Lifu; Kim, Seoyoung; Xie, Qian; Liu, Chao; Heumüller, Thomas; Liu, Zuoji; Zhang, Youhui; Wu, Feiyan; Yang, Changduk; et al. (Angewandte Chemie International Edition, 2022)
Although ternary organic solar cells (OSCs) have unique advantages in improving device performance, the morphology assembly in the ternary-phase would be more uncertain or complex than that in the binary-phase. Here, we propose a new concept of oligomer-assisted photoactive layers for high-performance OSCs. The formed alloy-like phase of the oligomer : host polymer blend enabled the oligomer-assisted OSCs to fuse the advantages of both binary and ternary devices, exhibiting substantially enhanced performance and stability compared to the control devices. With the addition of oligomers, outstanding efficiencies of 17.33 % for a PM6 : Y6 device, 18.32 % for a PM6 : BTP-eC9 device, and 17.13 % for a PM6/Y6 pseudo-bilayer device were achieved, all of which are one of the highest values in their corresponding fields. The improved performance originated from the downshift energy levels, enhanced light absorption, optimized blend morphology, favorable charge dynamics, and reduced non-radiative energy loss.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Organic Solar Cells; Performance; Stability